Development and nutrition of black wattle seedlings (Acacia mearnsii de Wild. De Wild.) in poultry litter substrate (Revista de Ciências Agroveterinárias, 2018)
We evaluated the development and the nutritional status of Acacia mearnsii De Wild. seedlings produced in four organic substrates with poultry litter base, distributed in percentage terms: T1: 25CA:50S:25A; T2: 50CA25S25A; T3: 25CA75S and T4: 100SC (CA: poultry litter; S: soil; A: sand; SC: commercial substrate), in tubes of 125 cm3 conducted in greenhouse / shade area. The best results, to the morphological variables height, stem diameter, number of leaves, dry mass of roots and total, were obtained in commercial substrate and in between 25 to 50% of poultry litter with clay soil and sand. The N and Mg contents (shoot and roots) and P and K (shoot) were not influenced by substrates. In the roots, the P content was greater on treatment with biggest proportion of clay soil. The K, in the roots, had the highest levels in substrates composed of 25 to 50% of poultry litter and commercial substrate. For Ca, the contents in shoots were higher than roots, mainly in the substrates with up to 50% of poultry litter. In the roots, the proportion of poultry litter did not influence Ca. The tested substrates, generally, did not influence the nutritional status of the seedlings.
Keywords: alternative substrate; forest nutrition; forest specie; substrates for biological treatment